The Impact of Private Equity and Venture Capital Funds on post-IPO Operational and Financial Performance in Brazilian invested companies - Bianca Piloto Sincerre; Joelson Sampaio; Rubéns Famá; Eduardo .S Flores (BBR: Brazilian Business Review)
The present article seeks to analyze the legacy and its persistence over time in terms of financing and operational policies and financial performance, of companies invested by Private Equity and Venture Capital funds (PE/VC). The PE/VC industry is characterized by the function of identifying companies with large return potentials and that grow arithmetically – due to capital constraints – to provide adequate and necessary sources of capital and experience for exponential growth. In this study, we used four measures that relate to companies’ financial policies and their persistence over time: i) cash & equivalents; ii) leverage; iii) Return on Assets (ROA); and iv) sales growth. The results suggest that PE / VC invested companies imply higher levels of cash & equivalents and are associated with a lower level of leverage during the first 5 years after the IPO. In addition, companies financed by PE/VC funds show higher profitability and higher sales growth compared to non-invested companies in the short term, i.e., in the first 3 years after the IPO.